Solusi Conduct Disorder Menurut Al-Qur’an Surah Al-A’raf : 33 - Pohan, Arnita Suryani (TSAQOFAH, 2023)
Conduct Disorder or behavioral disorder in the Qur'an, with the formulation of the problem, What is the meaning of Conduct Disorder, What is the mujmal meaning of Q.S Al-A'raf verse 33, and what is the solution to conduct disorder. This research is a library research (Library Research), by collecting data related to this research, then described based on the data obtained. And using the Comparative interpretation method, namely by including three interpretations from different books then analyzing and examining what are the differences and similarities of the problem. The results of the study show that there are three solutions to conduct disorder, namely parenting parents, a good environment and pious association and the third is repentance contained in Q.S At-Tahrim verse 8. Then the author includes interpretations of the three commentary books namely Al-Misbah , Al-Munir and An-Nur. As for the more dominant of the three books of commentary, Al-Munir's book of commentaries, namely, there are many explanations that point to Islamic psychology.